Assessement of ingested fluoride from toothpaste during brushing in some Egyptian children - Hadeel Ahmed Ibrahim Elshafei; Mervat Abdelmoneim Rashed; Mohammed AbuElyazeed Ahmed; Norhan Abdelwahab Eldokky (Cairo : Hadeel Ahmed Ibrahim Elshafei, 2010)
The objective of this study was to measure the estimated amount of fluoride ingested from the toothpaste by a group of 60 Egyptian children aged 4-6 years old during brushing their teeth and to evaluate the effect of the parent's assistance during brushing on the amount of fluoride ingested by these children. They were divided into 2 groups of 30 children
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Pedodontics
Issued also as CD
Keywords: Dental Caries; Dental fluorosis; Fluoride dentifrice